(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The specific of teaching of the special disciplines on artistically-graphic faculties, and also specific of educationalbusiness relations of teacher and students is examined in the article. To one of main in this process an author sees the necessity of taking into account in the educational process of perceptible factor, and also the active use of de bene esse-vivid arsenal.